The Effect of Macroeconomics Variables on Islamic Bank Stability During COVID-19 Pandemic: Evidence From Indonesia - Ikrima Hamda; Barianto Nurasri Sudarmawan (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
Research explores the impact of COVID-19 on banking has been carried out by previous researchers in the last two years. However, there are no researchers who specifically discuss about banking stability during the COVID-19 pandemic which is related to macroeconomic relaxation during the COVID-19 pandemic. The purpose of this research was to explore the macroeconomic influence on banking stability during COVID-19 in anticipation of a similar shock. This study uses Ordinary Least Square (OLS) method to describe macroeconomic factors as independent variables and control variables on the z-score as the dependent variable. The results of the study showing the GDP variable has a significant negative effect, while the BI Rate and Exchange Rate variables have a significant positive effect on the stability of Islamic banking during the COVID-19 pandemic. As well as inflation and JUB variables show insignificant results. This finding implies that macroeconomics has an influence on bank stability so when the macroeconomic have shock, the government is required to make right strategy, either in the form of comprehensive policies, to maintain bank stability. These findings established the Government has succeeded in adopting several policies that have proven effective in running the economy which have an impact on bank stability during COVID-19 pandemic.